Preparation process of rotary blowout preventer rubber core made of high-strength polymer material
By using a composite material of hydrogenated nitrile rubber, epoxidized natural rubber, aramid pulp and graphene quantum dots in the rubber core of the rotating blowout preventer, the problem of the deterioration of the strength of the existing rubber core under the action of ultraviolet rays is solved. Achieving higher strength and UV resistance, suitable for drilling high-pressure and high-temperature environments.
Patent Information
- Application Number
- CN202411466770.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The strength of the existing rotary blowout preventer core is significantly deteriorated under the action of ultraviolet rays, and its wear resistance and high temperature resistance are insufficient, making it difficult to meet the high pressure and high temperature requirements during drilling.
A high-strength polymer material preparation process is adopted, by mixing hydrogenated nitrile rubber with zinc oxide, stearic acid, cross-linking agent TAIC and vulcanizing agent DCP, and then adding epoxidized natural rubber and aramid pulp. The reactants of graphene quantum dots are used as reinforcing anti-aging agents. After full vulcanization and shaping treatment, a rotating blowout preventer rubber core with excellent strength and UV resistance is prepared.
The strength and ultraviolet resistance of the rubber core of the rotating blowout preventer are significantly improved, which can better adapt to the high-pressure and high-temperature environment during drilling and extend the service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of a rotary blowout preventer rubber core modification process, and more specifically, to a rotary blowout preventer rubber core preparation process of a high-strength polymer material. Background Art
[0002] During the drilling process of oil or natural gas, if high-pressure fluid in the formation is encountered, the high-pressure fluid in the formation will flow into the wellbore, causing well gushing or blowout. Therefore, during the drilling process, a blowout preventer is needed to limit the occurrence of blowouts. Therefore, the design of the blowout preventer is also required to be able to adapt to high pressure and allow the drill pipe to rotate.
[0003] Among them, the rubber core is one of the important components of the blowout preventer, which needs to have excellent wear resistance, oil resistance and high temperature resistance to be suitable for drilling procedures. For this reason, the rubber core is usually prepared with fluororubber, hydrogenated nitrile rubber or nitrile rubber as the main body. Compared with nitrile rubber or fluororubber, hydrogenated nitrile rubber has better high temperature resistance and wear resistance.
[0004] However, due to the particularity of the driller's work, the rotary blowout preventer rubber core is required to have extremely good strength. At the same time, when the hydrogenated nitrile rubber is exposed to the environment for a long time, under the influence of ultraviolet rays, the strength of the hydrogenated nitrile rubber will significantly deteriorate. Therefore, there is an urgent need for a hydrogenated nitrile rubber with both excellent strength and UV resistance to prepare the rotary blowout preventer rubber core. Summary of the invention
[0005] In order to improve the defects of conventional hydrogenated nitrile rubber, namely, insufficient strength and poor UV resistance, the present application provides a process for preparing a rotary blowout preventer rubber core made of a high-strength polymer material.
[0006] The present application provides a high-strength polymer material rotary blowout preventer rubber core preparation process, which adopts the following technical solution: A process for preparing a rotary blowout preventer rubber core made of high-strength polymer material comprises the following steps: Step 1, firstly, kneading the hydrogenated nitrile rubber, and then sequentially adding zinc oxide, stearic acid, crosslinking agent TAIC and vulcanizing agent DCP, and kneading evenly to obtain a hydrogenated nitrile rubber base material; Step 2, adding a reinforcing antioxidant to the hydrogenated nitrile rubber base material, and then rolling and breaking it up evenly in a triangle package to obtain a hydrogenated nitrile rubber composite material, wherein the reinforcing antioxidant is a reactant of epoxidized natural rubber, aramid pulp and graphene quantum dots; Step 3: Fully vulcanize and shape the hydrogenated nitrile rubber composite material at 160-180° C. and 10-20 MPa to obtain a rotary blowout preventer rubber core.
[0007] Fiber reinforcement is a commonly used method of rubber reinforcement. Compared with synthetic fibers such as nylon fiber and polyester fiber, aramid pulp not only has higher strength and modulus, but also has a larger specific surface area due to its rich fine fibers, which has more binding sites with rubber and thus has better bonding ability with rubber.
[0008] Graphene quantum dots are more efficient in capturing photons in the short wavelength region due to π-π* electronic transitions. It exhibits a strong optical absorption effect in the ultraviolet A (UVA, 320-400 nanometers) and ultraviolet B (UVB, 280-320 nanometers) regions, and then emits it in the form of fluorescence, thereby reducing the impact of ultraviolet rays on hydrogenated nitrile rubber, thereby improving the anti-ultraviolet performance of the rotary blowout preventer rubber core. At the same time, graphene quantum dots also have a certain reinforcement effect.
[0009] However, due to the complexity of aramid pulp fibers, the friction generated during processing can easily lead to electrostatic adsorption between fine fibers, which can cause aramid pulp to agglomerate. In addition, aramid pulp and hydrogenated nitrile rubber have significant differences, making it difficult to disperse in the hydrogenated nitrile rubber matrix and effectively achieve its reinforcement effect. Similarly, graphene quantum dots also have the problem of agglomeration.
[0010] Epoxidized natural rubber and hydrogenated nitrile rubber have certain structural similarities and compatibility, and both have high saturation and polarity. Therefore, when aramid pulp and graphene quantum dots are compounded with epoxidized natural rubber, the epoxidized natural rubber can play the role of building a bridge, thereby further improving the strength and UV resistance of the rotary blowout preventer rubber core.
[0011] Preferably, the hydrogenated nitrile rubber composite material comprises the following raw materials in parts by weight: 90-110 parts of hydrogenated nitrile rubber, 4-6 parts of zinc oxide, 1-2 parts of stearic acid, 1-3 parts of crosslinking agent TAIC, 4-6 parts of vulcanizing agent DCP and 12-18 parts of reinforcing antioxidant, wherein the reinforcing antioxidant is a reactant of epoxidized natural rubber, aramid pulp and graphene quantum dots.
[0012] Preferably, the reinforcing antioxidant comprises the following raw materials in parts by mass: 40-60 parts of epoxidized natural rubber, 40-60 parts of aramid pulp and 20-30 parts of graphene quantum dot solution.
[0013] When the components of the reinforcing antioxidant adopt the above mass ratio, the prepared rotary blowout preventer rubber core will have better strength and UV resistance.
[0014] Preferably, the preparation method of the graphene quantum dot solution is: First, place citric acid in a weighing bottle, then heat it in an oil bath at 170-180°C for 20-40 minutes, then transfer it to a sodium hydroxide solution, ultrasonicate it for 20-40 minutes until it is completely dissolved, filter it with a 0.22μm microporous filter membrane, and dialyze the filtrate in a 3000Da dialysis bag. Change the water every 1 hour until the liquid outside the dialysis bag is neutral, and finally obtain a graphene quantum dot solution.
[0015] Preferably, in the method for preparing the graphene quantum dot solution, the added amount of citric acid is 0.4-0.6 g, the sodium hydroxide solution is 40-60 ml of sodium hydroxide aqueous solution, and the concentration of the sodium hydroxide aqueous solution is 10 mg / L.
[0016] Preferably, the preparation method of the reinforcing antioxidant is: Firstly, aramid pulp is reacted with graphene quantum dot solution to obtain graphene quantum dot-aramid composite pulp; then, epoxidized natural rubber is refined on a mixer, flattened and then slowly added with graphene quantum dot-aramid composite pulp for mixing, and finally, triangle packages are formed and rolled until evenly dispersed to obtain a reinforcing antioxidant.
[0017] The graphene quantum dots in the present application are carbonized by a bottom-up hydrothermal citric acid method using citric acid as a carbon source, and small-sized graphene quantum dots are formed during incomplete carbonization. The graphene quantum dots contain more oxygen-containing functional groups, and such oxygen-containing functional groups can form hydrogen bonds with the amide groups on the surface of the swollen aramid pulp, thereby loading the graphene quantum dots on the surface of the aramid pulp, and then achieving a synergistic barrier agglomeration effect with the aramid pulp, thereby further improving the strength and UV resistance of the rotary blowout preventer rubber core.
[0018] Preferably, the method for preparing the graphene quantum dot-aramid composite pulp comprises the following steps: S1. First, immerse the aramid pulp in ethanol, and then add deionized water to stir thoroughly at a stirring speed of 400-500 r / min for 1-3 h; S2. When the aramid pulp is fully swollen, add ammonia water and continue stirring for 10-20 minutes, then add the graphene quantum dot solution and stir it thoroughly at a stirring speed of 400-500 r / min for 4-6 hours; S3. After stirring, centrifuge at a speed of 4000-5000 r / min for 20-40 min, then wash with water and alcohol, and finally dry at 70-90° C. to obtain graphene quantum dot-aramid composite pulp.
[0019] Preferably, the volume ratio of the ethanol, deionized water and ammonia water is (1-3): (0.5-1.5): (0.05-0.15).
[0020] In summary, this application has the following beneficial effects: 1. Fiber reinforcement is a commonly used method of rubber reinforcement. Compared with synthetic fibers such as nylon fiber and polyester fiber, aramid pulp not only has higher strength and modulus, but also has a larger specific surface area due to its rich fine fibers, which has more binding sites with rubber and thus has better bonding ability with rubber.
[0021] Graphene quantum dots are more efficient in capturing photons in the short wavelength region due to π-π* electronic transitions. It exhibits extremely strong optical absorption in the ultraviolet A (UVA, 320-400 nanometers) and ultraviolet B (UVB, 280-320 nanometers) regions, and then discharges it in the form of fluorescence, thereby reducing the impact of ultraviolet rays on hydrogenated nitrile rubber, thereby improving the anti-ultraviolet performance of the rotary blowout preventer rubber core. At the same time, graphene quantum dots also have a certain reinforcement effect.
[0022] 2. Since the fibers of aramid pulp are intricate and the friction generated during processing can easily lead to electrostatic adsorption between fine fibers, causing the aramid pulp to agglomerate. In addition, there are significant differences between aramid pulp and hydrogenated nitrile rubber, making it difficult to disperse in the hydrogenated nitrile rubber matrix and effectively achieve its reinforcement effect. Similarly, graphene quantum dots also have the problem of agglomeration.
[0023] Epoxidized natural rubber and hydrogenated nitrile rubber have certain structural similarities and compatibility, and both have high saturation and polarity. Therefore, when aramid pulp and graphene quantum dots are compounded with epoxidized natural rubber, the epoxidized natural rubber can play the role of building a bridge, thereby further improving the strength and UV resistance of the rotary blowout preventer rubber core.
[0024] 3. The graphene quantum dots in the present application are carbonized by a bottom-up hydrothermal citric acid method using citric acid as a carbon source, and small-sized graphene quantum dots are formed during incomplete carbonization. The graphene quantum dots contain more oxygen-containing functional groups, and these oxygen-containing functional groups can form hydrogen bonds with the amide groups on the surface of the swollen aramid pulp, thereby loading the graphene quantum dots on the surface of the aramid pulp, and then achieving a synergistic barrier agglomeration effect with the aramid pulp, thereby further improving the strength and UV resistance of the rotary blowout preventer rubber core. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with Examples 1-6 and Comparative Examples 1-2.
[0026] raw material Hydrogenated nitrile rubber CAS: 308068-83-9; zinc oxide CAS: 1314-13-2; stearic acid CAS: 57-11-4; crosslinking agent TAIC Neutralization Chemical; vulcanizing agent DCP Junteng Chemical; epoxidized natural rubber neutralization chemical ENR50; aramid pulp Shuobang New Materials; citric acid CAS: 77-92-9; sodium hydroxide CAS: 1310-73-2; ethanol CAS: 64-17-5; ammonia CAS: 1336-21-6.
[0027] Example Example 1 A process for preparing a rotary blowout preventer rubber core made of high-strength polymer material comprises the following steps: Step 1: First, 100 g of hydrogenated nitrile rubber was kneaded, and then 5 kg of zinc oxide, 1.5 g of stearic acid, 2 g of crosslinking agent TAIC and 5 g of vulcanizing agent DCP were added in sequence, and the mixture was evenly kneaded to obtain a hydrogenated nitrile rubber base material; Step 2, adding 5g of reinforcing antioxidant to the hydrogenated nitrile rubber base material, and then rolling and breaking it up evenly in a triangle package to obtain a hydrogenated nitrile rubber composite material; The reinforcing antioxidant is composed of epoxidized natural rubber, aramid pulp and graphene quantum dots, and the mass ratio of the epoxidized natural rubber, aramid pulp and graphene quantum dots is 50:50:25.
[0028] The preparation method of the reinforcing antioxidant is as follows: firstly, the epoxidized natural rubber is refined on a mixer, and after being flattened, graphene quantum dots and aramid pulp are slowly added for mixing, and finally, a triangle package is formed and rolled until it is evenly dispersed to obtain the reinforcing antioxidant.
[0029] Among them, the preparation method of graphene quantum dots is as follows: first, 0.5g of citric acid is placed in a weighing bottle, then placed in an oil bath at 175°C and heated for 30 minutes, then transferred to 50ml of sodium hydroxide aqueous solution, the concentration of the sodium hydroxide aqueous solution is 10mg / L, ultrasonicated for 30 minutes until it is completely dissolved, filtered with a 0.22μm microporous filter membrane, and the filtrate is placed in a 3000Da dialysis bag for dialyzing, and the water is changed every 1h until the liquid outside the dialysis bag is neutral, and finally the product is dried at 80°C to obtain graphene quantum dots.
[0030] Step 3: Fully vulcanize and shape the hydrogenated nitrile rubber composite material at 170° C. and 15 MPa to obtain a rotary blowout preventer rubber core.
[0031] Example 2 The difference from Example 1 is that aramid pulp is no longer added.
[0032] Example 3 The difference from Example 1 is that graphene quantum dots are no longer added.
[0033] Example 4 A process for preparing a rotary blowout preventer rubber core made of high-strength polymer material comprises the following steps: Step 1: First, 100 g of hydrogenated nitrile rubber was kneaded, and then 5 kg of zinc oxide, 1.5 g of stearic acid, 2 g of crosslinking agent TAIC and 5 g of vulcanizing agent DCP were added in sequence, and the mixture was evenly kneaded to obtain a hydrogenated nitrile rubber base material; Step 2, adding 15g of reinforcing antioxidant to the hydrogenated nitrile rubber base material, and then rolling and breaking it up evenly in a triangle package to obtain a hydrogenated nitrile rubber composite material; The reinforcing antioxidant is composed of epoxidized natural rubber, aramid pulp and graphene quantum dots, and the mass ratio of the epoxidized natural rubber, aramid pulp and graphene quantum dots is 50:50:25.
[0034] The preparation method of the reinforcing antioxidant is as follows: firstly, the epoxidized natural rubber is refined on a mixer, and after being flattened, graphene quantum dots and aramid pulp are slowly added for mixing, and finally, a triangle package is formed and rolled until it is evenly dispersed to obtain the reinforcing antioxidant; The preparation method of graphene quantum dot-aramid composite pulp comprises the following steps: S1. First, immerse the aramid pulp in ethanol, and then add deionized water to stir thoroughly at a stirring speed of 450 r / min for 2 h; S2. When the aramid pulp is fully swollen, add ammonia water and continue stirring for 15 minutes, then add the graphene quantum dot solution and stir it thoroughly at a stirring speed of 450 r / min for 5 hours; S3, after the stirring is completed, centrifuge at a speed of 4500r / min for 30min, then wash with water and alcohol, and finally dry at 80°C to obtain graphene quantum dot-aramid composite pulp; The volume ratio of ethanol, deionized water and ammonia water is 2:1:0.1, and the amount of ethanol is such that the aramid pulp is completely immersed, which can be specifically set to 100 g / L of aramid pulp.
[0035] Among them, the preparation method of graphene quantum dots is as follows: first, 0.5g of citric acid is placed in a weighing bottle, then placed in an oil bath at 175°C and heated for 30 minutes, then transferred to 50ml of sodium hydroxide aqueous solution, the concentration of the sodium hydroxide aqueous solution is 10mg / L, ultrasonicated for 30 minutes until it is completely dissolved, filtered with a 0.22μm microporous filter membrane, and the filtrate is placed in a 3000Da dialysis bag for dialyzing, and the water is changed every 1h until the liquid outside the dialysis bag is neutral, and finally the product is dried at 80°C to obtain graphene quantum dots.
[0036] Step 3: Fully vulcanize and shape the hydrogenated nitrile rubber composite material at 170° C. and 15 MPa to obtain a rotary blowout preventer rubber core.
[0037] Embodiment 5-6 The difference from Example 4 is that the mass ratios of epoxidized natural rubber, aramid pulp and graphene quantum dots are different, as shown in Table 1.
[0038] Table 1 Mass ratio of each component of the reinforcing antioxidant in Examples 4-6
[0039] Comparative Example Comparative Example 1 The difference from Example 1 is that no reinforcing antioxidant is added.
[0040] Comparative Example 2 The difference from Example 1 is that no epoxidized natural rubber is added.
[0041] Performance testing Detection Methods 1. Tear strength test Three samples were taken from Examples 1-6 and Comparative Examples 1-2, respectively, and the tear strength of the samples was tested according to GB / T 12829-2006 "Determination of tear strength of small specimens (Telft specimens) of vulcanized rubber or thermoplastic rubber" and the average value was taken.
[0042] 2. Anti-ultraviolet performance test Three samples were taken from Examples 1-6 and Comparative Examples 1-2 respectively, and then the samples were subjected to ultraviolet aging treatment in accordance with GB / T16585-1996 "Artificial Climate Aging Test for Vulcanized Rubber Using Fluorescent Ultraviolet Lamp", and then the aged products were subjected to a tear strength test, with the same test standards as above. Finally, the tear strength change was calculated and the average value was taken.
[0043] Tear strength change value = (original tear strength - tear strength after aging / original tear strength) × 100%.
[0044] The test data are shown in Table 2.
[0045] Table 2 Test data table of Examples 1-6 and Comparative Examples 1-2
[0046] With reference to Example 1 and Comparative Example 1 and in combination with Table 2, it can be seen that, relative to Comparative Example 1, the tear strength of Example 1 is significantly improved, and at the same time, the tear strength change value of Example 1 is also significantly reduced, which indicates that the addition of reinforcing antioxidants can effectively improve the strength and UV resistance of hydrogenated nitrile rubber.
[0047] Referring to Examples 1-3 and Comparative Example 2 and in combination with Table 2, it can be seen that the tear strength of Example 2 is significantly reduced compared to Example 1, which indicates that aramid pulp is the main factor in improving the strength of hydrogenated nitrile rubber.
[0048] Compared with Example 1, the tear strength of Example 2 is slightly decreased, and the tear strength change value of Example 2 is significantly increased, which shows that graphene quantum dots can improve the strength and UV resistance of hydrogenated nitrile rubber at the same time.
[0049] Compared with Example 1, the tear strength of Example 2 is significantly reduced, and the tear strength change of Example 2 is also significantly increased, which shows that the addition of epoxidized natural rubber can effectively improve the strength and UV resistance of hydrogenated nitrile rubber.
[0050] The reason is that fiber reinforcement is a commonly used method of rubber reinforcement. Compared with synthetic fibers such as nylon fiber and polyester fiber, aramid pulp not only has higher strength and modulus, but also has a larger specific surface area due to its rich fine fibers, which has more binding sites with rubber and thus has better bonding ability with rubber.
[0051] Graphene quantum dots are more efficient in capturing photons in the short wavelength region due to π-π* electronic transitions. It exhibits extremely strong optical absorption in the ultraviolet A (UVA, 320-400 nanometers) and ultraviolet B (UVB, 280-320 nanometers) regions, and then discharges it in the form of fluorescence, thereby reducing the impact of ultraviolet rays on hydrogenated nitrile rubber, thereby improving the anti-ultraviolet performance of the rotary blowout preventer rubber core. At the same time, graphene quantum dots also have a certain reinforcement effect.
[0052] However, due to the complexity of aramid pulp fibers and the friction generated during processing, it is easy to cause electrostatic adsorption between small fibers, resulting in agglomeration of aramid pulp. In addition, there are significant differences between aramid pulp and hydrogenated nitrile rubber, making it difficult to disperse in the hydrogenated nitrile rubber matrix and effectively achieve its reinforcement effect. Similarly, graphene quantum dots also have the problem of agglomeration.
[0053] Epoxidized natural rubber and hydrogenated nitrile rubber have certain structural similarities and compatibility, and both have high saturation and polarity. Therefore, when aramid pulp and graphene quantum dots are compounded with epoxidized natural rubber, the epoxidized natural rubber can play the role of building a bridge, thereby further improving the strength and UV resistance of hydrogenated nitrile rubber.
[0054] Referring to Example 1 and Example 4 and combining with Table 2, it can be seen that compared with Example 1, the tear strength of Example 4 is further improved, and the tear change of Example 4 is further reduced. This shows that, compared with adding graphene quantum dots to aramid pulp separately, preparing graphene quantum dots and aramid pulp into graphene quantum dots-aramid composite pulp can further improve the strength and UV resistance of hydrogenated nitrile rubber.
[0055] The reason is that the graphene quantum dots in the present application are carbonized by a bottom-up hydrothermal citric acid method using citric acid as a carbon source, and small-sized graphene quantum dots are formed during incomplete carbonization. The graphene quantum dots contain more oxygen-containing functional groups, and such oxygen-containing functional groups can form hydrogen bonds with the amide groups on the surface of the swollen aramid pulp, thereby loading the graphene quantum dots on the surface of the aramid pulp, and then achieving a synergistic barrier agglomeration effect with the aramid pulp, thereby further improving the strength and UV resistance of the rotary blowout preventer rubber core.
[0056] With reference to Examples 4-6 and in combination with Table 2, it can be seen that, relative to Example 4, the tear strength of Examples 5-6 is slightly decreased, and the change in tear strength of Examples 5-6 is slightly increased. This indicates that when the components of the reinforcing antioxidant adopt the mass proportion of Example 4, the prepared hydrogenated nitrile rubber will have better strength and UV resistance.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for preparing a rotary blowout preventer rubber core made of high-strength polymer material, characterized in that: The following steps are involved: Step 1: firstly, knead the hydrogenated nitrile rubber, and then sequentially add zinc oxide, stearic acid, crosslinking agent TAIC and vulcanizing agent DCP, and knead evenly to obtain a hydrogenated nitrile rubber base material; Step 2, adding a reinforcing antioxidant to the hydrogenated nitrile rubber base material, and then rolling and breaking it up evenly in a triangle package to obtain a hydrogenated nitrile rubber composite material, wherein the reinforcing antioxidant is a reactant of epoxidized natural rubber, aramid pulp and graphene quantum dots; Step 3: Fully vulcanize and shape the hydrogenated nitrile rubber composite material at 160-180° C. and 10-20 MPa to obtain a rotary blowout preventer rubber core.
2. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 1, characterized in that: The hydrogenated nitrile rubber composite material comprises the following raw materials in parts by weight: 90-110 parts of hydrogenated nitrile rubber, 4-6 parts of zinc oxide, 1-2 parts of stearic acid, 1-3 parts of crosslinking agent TAIC, 4-6 parts of vulcanizing agent DCP and 12-18 parts of reinforcing antioxidant, wherein the reinforcing antioxidant is a reactant of epoxidized natural rubber, aramid pulp and graphene quantum dots.
3. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 1, characterized in that: The reinforcing antioxidant comprises the following raw materials in parts by mass: 40-60 parts of epoxidized natural rubber, 40-60 parts of aramid pulp and 20-30 parts of graphene quantum dot solution.
4. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 3, characterized in that: The preparation method of the graphene quantum dot solution is: First, place citric acid in a weighing bottle, then heat it in an oil bath at 170-180°C for 20-40 minutes, then transfer it to a sodium hydroxide solution, ultrasonicate it for 20-40 minutes until it is completely dissolved, filter it with a 0.22μm microporous filter membrane, and dialyze the filtrate in a 3000Da dialysis bag. Change the water every 1 hour until the liquid outside the dialysis bag is neutral, and finally obtain a graphene quantum dot solution.
5. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 4, characterized in that: In the method for preparing the graphene quantum dot solution, the added amount of citric acid is 0.4-0.6 g, the sodium hydroxide solution is 40-60 ml of sodium hydroxide aqueous solution, and the concentration of the sodium hydroxide aqueous solution is 10 mg / L.
6. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 4, characterized in that: The preparation method of the reinforcing antioxidant is: Firstly, aramid pulp is reacted with graphene quantum dot solution to obtain graphene quantum dot-aramid composite pulp; then, epoxidized natural rubber is refined on a mixer, flattened and then slowly added with graphene quantum dot-aramid composite pulp for mixing, and finally, triangle packages are formed and rolled until evenly dispersed to obtain a reinforcing antioxidant.
7. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 6, characterized in that: The preparation method of the graphene quantum dot-aramid composite pulp comprises the following steps: S1. First, immerse the aramid pulp in ethanol, and then add deionized water to stir thoroughly at a stirring speed of 400-500 r / min for 1-3 h; S2. When the aramid pulp is fully swollen, add ammonia water and continue stirring for 10-20 minutes, then add the graphene quantum dot solution and stir it thoroughly at a stirring speed of 400-500 r / min for 4-6 hours; S3. After stirring, centrifuge at a speed of 4000-5000 r / min for 20-40 min, then wash with water and alcohol, and finally dry at 70-90° C. to obtain graphene quantum dot-aramid composite pulp.
8. The process for preparing a rotary blowout preventer rubber core made of high-strength polymer material according to claim 7, characterized in that: The volume ratio of the ethanol, deionized water and ammonia water is (1-3): (0.5-1.5): (0.05-0.15).
Citation Information
Patent Citations
High-temperature-resistant rubber core for rotating control head and preparing method thereof
CN105694162A
Graphene quantum dot / rubber nano composite material
CN107501646A
Special rotary blowout preventer rubber core material for oil-based mud
CN111393730A
Rubber composition, preparation method thereof and application of rubber composition in air cavity rubber pad of air compressor
CN115873315A